Improved protective efficacy of a species-specific DNA vaccine encoding mycolyl-transferase Ag85A from Mycobacterium ulcerans by homologous protein boosting. - Audrey Tanghe; Jean-Pierre Dangy; Gerd Pluschke; Kris Huygen (Public Library of Science (PLoS), 2008)
Vaccination with plasmid DNA encoding Ag85A from M. bovis BCG can partially protect C57BL/6 mice against a subsequent footpad challenge with M. ulcerans. Unfortunately, this cross-reactive protection is insufficient to completely control the infection. Although genes encoding Ag85A from M. bovis BCG (identical to genes from M. tuberculosis) and from M. ulcerans are highly conserved, minor sequence differences exist, and use of the specific gene of M. ulcerans could possibly result in a more potent vaccine. Here we report on a comparison of immunogenicity and protective efficacy in C57BL/6 mice of Ag85A from M. tuberculosis and M. ulcerans, administered as a plasmid DNA vaccine, as a recombinant protein vaccine in adjuvant or as a combined DNA prime-protein boost vaccine. All three vaccination formulations induced cross-reactive humoral and cell-mediated immune responses, although species-specific Th1 type T cell epitopes could be identified in both the NH2-terminal region and the COOH-terminal region of the antigens. This partial species-specificity was reflected in a higher--albeit not sustained--protective efficacy of the M. ulcerans than of the M. tuberculosis vaccine, particularly when administered using the DNA prime-protein boost protocol.